Complete mitochondrial genome of spined sleeper Eleotris oxycephala (Perciformes, Eleotridae) and phylogenetic consideration. (October 2015) - Xia, Aijun; Zhong, Liqiang; Chen, Xiaohui; Bian, Wenji; Zhang, Tongqing; Shi, Yangbai
Abstract: The complete mitochondrial genome of Eleotris oxycephala was determined to be 16, 527 bp in length with (A + T) content of 53%, and it consists of 13 protein-coding genes, 22 tRNAs, 2 ribosomal RNAs, and a control region. The gene composition and the structural arrangement of the E . oxycephala complete mtDNA were identical to most of other vertebrates. Phylogenetic analysis based on different sequences of species of the Gobioidei suborder and different methods showed that E. oxycephala formed a cluster with Eleotris acanthopoma and Eleotridae were divided into two clades. Furthermore, extensive taxon sampling and more molecular information are needed to confirm the phylogenetic relationships among the Gobioidei. Highlights: The complete mitogenome of Eleotris oxycephala was determined and annotated. Genome organization and stucture of the E. oxycephala mitochondrial genome is similar to other teleosts. Phylogenetic analysis showed two Eleotridae clades.